PENGARUH PENYULUHAN MENGGUNAKAN MEDIA X-BANNER TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT - Kirmawati, Rossy Rocella; Rahmawati, Ida; Nurwati, Bunga; Sab'atul Habibah, Siti (JURNAL TERAPIS GIGI DAN MULUT, 2025)
The number of dental and oral problems in Indonesia is still very high, namely 94.7% regarding tooth brushing behavior. Efforts to overcome this problem are health education. This study aims to analyze the effect of counseling using X-banner media on children's knowledge about dental and oral health. The research method used is one group pretest-posttest design. The research sample was selected using a purposive sampling technique and there were 49 people. Data analysis used the paired sample t-test. The research results showed that the p-value was 0.000 < α 0.05 with an average pretest knowledge value of 7.2 and posttest of 12.31. The conclusion is that there is an influence of education using x-banners on knowledge of dental and oral health.